First record of the Northern brown shrimp, Farfantepenaeus aztecus (Ives, 1891) (Crustacea: Decapoda: Penaeidae) in the South Adriatic Sea, Montenegro - MARKOVIĆ, O.; GÖKOĞLU, M.; PETOVIĆ, S.; MANDIĆ, M. (Mediterranean Marine Science, 2013)
A single adult female specimen of the Northern brown shrimp, Farfantepenaeus aztecus, a species native to the western Atlantic coasts, was caught in Boka kotorska bay (southern Adriatic Sea) on 19 September 2013. This is the first record of this alien species in the Adriatic Sea.